Morpho-Biometric Evaluation of the Genetic Diversity of Local Chicken Ecotypes in Four Regions (Centre-East, Sahel, Centre-North and South-West) of Burkina Faso - Yacouba , Zare; Isidore, Gnanda B.; Isidore, Houaga; Michel, Kere; Boureima, Traore; Moussa, Zongo; Samuel, Bamouni; Apollinaire, Traore P.; Mahamoudou, Zangre; Romdhane, Rekaya; Joseph, Nianogo A. (International Journal of Poultry Science, 2021)
Background and Objective: Local chickens in Burkina Faso play a crucial role in income generation and food security, especially to the rural community and the most vulnerable groups. Genetic and phenotypic characterization of these local chicken ecotypes is sketchy. The objective of this study was to determine the morpho-biometric characteristics of local chicken “Konde” from the Centre-East and local ecotypes in the Sahel, Centre-North and South-West regions of Burkina Faso. Materials and Methods: A total of 1179 adult local chickens at six months of age were used for the study and sampled as followed: 406, 352, 285 and 136 chickens respectively from South-West, Centre-North, Sahel and Centre-East region. Results: The mean body weight of chicken was 1204.80±344.9 g and significantly affected by region and sex (p